2020
DOI: 10.3847/1538-4365/ab7a1a
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate, Extensive, and Practical Line List of Methane for the HITEMP Database

Abstract: A methane line list for the HITEMP spectroscopic database, covering 0-13,400 cm −1 (>746 nm), is presented. To create this compilation, ab initio line lists of 12 CH 4 from Rey et al. (2017) ApJ, 847, 105 (provided at separate temperatures in the TheoReTS information system), are now combined with HITRAN2016 methane data to produce a single line list suitable for high-temperature line-byline calculations up to 2000 K. An effective-temperature interpolation model was created in order to represent continuum-like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 123 publications
(186 reference statements)
1
107
1
Order By: Relevance
“…The total cross correlation signal is comparable to their work in terms of both strength (S/N = 4.6) and position in velocity space. The latter model, shown on the right panel, utilises the cross sections described in this paper and obtained from the HITEMP database (Hargreaves et al 2020). This model shows no significant correlation at the expected position of the planet (marked by dashed lines), thus we are unable to confirm the detection with this more recent line list.…”
Section: Ch 4 : Hd 102195 Bmentioning
confidence: 86%
See 4 more Smart Citations
“…The total cross correlation signal is comparable to their work in terms of both strength (S/N = 4.6) and position in velocity space. The latter model, shown on the right panel, utilises the cross sections described in this paper and obtained from the HITEMP database (Hargreaves et al 2020). This model shows no significant correlation at the expected position of the planet (marked by dashed lines), thus we are unable to confirm the detection with this more recent line list.…”
Section: Ch 4 : Hd 102195 Bmentioning
confidence: 86%
“…Our CH 4 cross section is calculated from the new HITEMP line list (Hargreaves et al 2020). This new addition to the HITEMP database utilises ab initio calculations with empirical corrections (Rey et al 2017) as well as the HITRAN2016 database (Gordon et al 2017) to produce a high temperature line list up to 2000 K. Hargreaves et al (2020) found good agreement with experimentally measured opacity at high temperature from Hargreaves et al (2015) and Wong et al (2019). The HITEMP line list uses effective lines allowing for efficient computation of opacities for such a large molecule with many billions of transitions.…”
Section: Chmentioning
confidence: 93%
See 3 more Smart Citations